PERBANDINGAN MODEL PEMBELAJARAN MIND MAPPING DAN SQ4R TERHADAP HASIL BELAJAR AKUNTANSI - Siska Dwi Anggraningrum; Tedy Rusman; Nurdin Muhammad (FKIP Unila, 2013)
This study aims to determine differences in learning outcomes Accounting through learning model Mind Mapping and SQ4R at high and low initial ability. Research using experimental methods with a comparative approach. The results showed:a) there are differences in accounting student learning outcomes through mind mapping and learning model SQ4R, evidenced by Sig obtained. 0.013 0.05. b) there is a difference between high and low prior knowledge on learning outcomes of accounting students, evidenced by Sig obtained. 0.032 0.05. c) model of mind mapping learning outcomes are higher than SQ4R at high initial ability, evidenced by Sig obtained. 0.026 than 0.05. d) the results of learning mind mapping models is lower than SQ4R at low initial ability, evidenced by Sig obtained. 0.000 than 0.05. e) There is interaction between the model of learning with prior knowledge of accounting students' learning outcomes, evidenced by Sig obtained. 0.000 0.05 Penelitian ini bertujuan mengetahui perbedaan hasil belajar Akuntansi melalui model pembelajaran Mind Mapping dan SQ4R pada kemampuan awal tinggi dan rendah. Penelitian menggunakan metode eksperimen dengan pendekatan komparatif. Hasil penelitian menunjukan: a) ada perbedaan hasil belajar akuntansi siswa melalui model pembelajaran mind mapping dan SQ4R, dibuktikan dengan diperoleh Sig. 0.013 0.05. b) ada perbedaan antara kemampuan awal tinggi dan rendah terhadap hasil belajar akuntansi siswa, dibuktikan dengan diperoleh Sig. 0.032 0.05. c) hasil belajar model mind mapping lebih tinggi daripada SQ4R pada kemampuan awal tinggi, dibuktikan dengan diperoleh Sig. 0,026 dari 0,05. d) hasil belajar model mind mapping lebih rendah daripada SQ4R pada kemampuan awal rendah, dibuktikan dengan diperoleh Sig. 0,000 dari 0,05. e) Ada interaksi antara model pembelajaran dengan kemampuan awal siswa terhadap hasil belajar akuntansi, dibuktikan dengan diperoleh Sig. 0.000 0.05. Kata kunci: model pembelajaran, mind mapping, SQ4R, kemampuan awal